A curvature-controllable, convex-mirror actuator based on carbon nanotube film composites. (January 2016) - Zhou, Zhiwei; Chen, Luzhuo; Liu, Changhong; Fan, Shoushan
Abstract: A novel round shape electrothermal actuator based on a bimorph structure with a cross-stacked superaligned carbon nanotube film and polydimethylsiloxane has been designed and fabricated. The coated silver film (100 nm thickness) makes the actuator surface like a mirror. Compared with common polymer nanocomposites based electrothermal actuators, our actuator exhibits a distinctive shape change. Due to the different coefficients of thermal expansion of the two material layers, it turns into a convex shape (a concave shape on the other surface) by using low electric field strengths such as < 200 V m −1 . The curvature of the convex shape can be controlled by the voltage precisely. It can lift almost four times of its own weight. The cyclic actuation test shows the excellent stability of the actuator (over 2000 times). Owing to the advantages of low driving voltages, muscle-like responses, distinctive shape changes, mirror-like surface, stability, we think the novel actuator will have great potential usages in various applications, such as artificial muscles, optical devices, microsensors, microrobots, and so on.